تنظير البطن في تشخيص وتدبير بعض الأمراض النسائية - النقري, محمد; صالح, حسن; زغيبة, ريم (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في مشفى الأسد الجامعي باللاذقية في قسم التوليد وأمراض النساء في الفترة ما بين 1/1/2002 – 1/6/2003 وتضمنت (100) حالة تنظير بطن لشكاوى مختلفة . كانت الاستطبابات كالتالي : 1ـ العقم. 2ـ الألم الحوضي . 3ـ التعقيم. 4ـ حالات متفرقة : ( لولب هاجر : حالتين) ـ (انقطاع طمث بدئي : 3 حالات )ـ( شك pco : 4 حالات ) نسبة العقم 59% من الحالات المدروسة . نسبة الموجودات المرضية في حالات العقم المدروسة 66% كالتالي : ـ خلل في نفوذية البوقين 32.2%. ـ التصاقات 16.9% . ـ اندومتريوز 8.47%. ـ مبيض متعدد الكيسات 8.47% . نسبة الألم الحوضي 27% من الحالات المدروسة . توزعت موجودات الألم الحوضي الحاد : ـ حمل هاجر 58.8%. ـ كيسة مبيض 29.4% . ـ جراب نازف 5.8%. ـ موجودات طبيعية 5.8% . توزعت موجودات الألم الحوضي المزمن : ـ التصاقات 50% ـ اندومتريوز 20% . ـ كيسة مبيض 10% ـ موجودات طبيعية 20% . نسبة التعقيم 5% من الحالات المدروسة . This research was conducted at AL-Assad University Hospital Lattakia, in the Obstetric and Gynecology department between 1/1/2002 – 1/6/2003, and on (100) cases of different complaints of laparoscopy. Indication. were as follow : 1- infertility. 2- pelvic pain. 3- sterilization. 4- distributed cases: (migrating spiral "2 cases") – initial amenorrhea "3 cases"- suspect of PCO "4 cases" ). The rate of infertility was (59%). The rate of morbid symptoms in studied cases of infertility (66%) was as following: - dyspenetration of tubes (32.2%). – adhensions (16.9%). - Endometriosis (8.47%) – poly cystic ovary (8.47%). The rate of pelvic pain was (27%). The cases of acute pelvic pain distributed as follow: - ectopic pregnancy (58.8%). – ovary cyst (29.4%). - Bleeder follicle (5.8%). – normal existings (5.8%). The cases of chronic pelvic pain distributed as follow: - Adhesions (50%). – endometriosis (20%). - ovary cyst (10%). – normal existings (20%). The rate of sterilization was (5%) of studied cases.